STUDY OF EFFICACY OF MEBARID - AN AYURVEDIC COMPOUND FORMULATION IN CHILDREN WITH ACUTE DIARRHEA - DR. S. BHUVANESHWARI; DR. DANGE SURESH VISHNU (International Journal of Pharma and Bio Sciences, 2012)
In clinical practice, nonspecific antidiarrheals (allopathic and ayurvedic) are most commonly used by clinicians along with routine treatment to hasten the recovery and to give psychological reassurance. This prospective observational study was carried out at two private clinics run by pediatricians to find out the effect of Mebarid, an ayurvedic polyherbal formulation on the severity and duration of diarrhea and to assess its safety. 100 children aged 2 y to 10 y with acute diarrhea and fulfilling selection criteria were enrolled and divided into two treatment groups viz , Control and Mebarid. Data collection was done using case report forms and questionnaires. Outcome Measures used were 1.Duration of diarrhea 2. Stool frequency 3. Improvement in stool consistency. Mebarid improved stool consistency significantly earlier (d1 vs. d1.5) as compared to control group (P<0.001).It also reduced the frequency of stools significantly (P<0.001).However, there was no significant difference in duration of diarrhea.